2008
DOI: 10.1371/journal.pone.0003439
|View full text |Cite
|
Sign up to set email alerts
|

Diaphanous-Related Formin 2 and Profilin I Are Required for Gastrulation Cell Movements

Abstract: Intensive cellular movements occur during gastrulation. These cellular movements rely heavily on dynamic actin assembly. Rho with its associated proteins, including the Rho-activated formin, Diaphanous, are key regulators of actin assembly in cellular protrusion and migration. However, the function of Diaphanous in gastrulation cell movements remains unclear. To study the role of Diaphanous in gastrulation, we isolated a partial zebrafish diaphanous-related formin 2 (zdia2) clone with its N-terminal regulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 81 publications
0
28
0
Order By: Relevance
“…Formins also have essential roles in physiological processes ranging from cell motility in the immune system (Yayoshi-Yamamoto et al, 2000;Eisenmann et al, 2007;Shi et al, 2009), to gastrulation and neural tube closure (Habas et al, 2001;Sato et al, 2006;Lai et al, 2008), heart morphogenesis (Iskratsch et al, 2010;Li et al, 2011), kidney morphogenesis (Brown et al, 2010;Boyer et al, 2011a;Boyer et al, 2011b), and dendritic spine formation in neurons. Some of these functions depend on the actin nucleation and elongation activities of formins (Bartolini et al, 2008;Andrés-Delgado et al, 2010;Madrid et al, 2010;Andrés-Delgado et al, 2012;Ramabhadran et al, 2012;Stastna et al, 2012), which have been demonstrated by investigating point mutations that impair in these activities Lu et al, 2007;Ramabhadran et al, 2012).…”
Section: Cellular Functions Of Forminsmentioning
confidence: 99%
“…Formins also have essential roles in physiological processes ranging from cell motility in the immune system (Yayoshi-Yamamoto et al, 2000;Eisenmann et al, 2007;Shi et al, 2009), to gastrulation and neural tube closure (Habas et al, 2001;Sato et al, 2006;Lai et al, 2008), heart morphogenesis (Iskratsch et al, 2010;Li et al, 2011), kidney morphogenesis (Brown et al, 2010;Boyer et al, 2011a;Boyer et al, 2011b), and dendritic spine formation in neurons. Some of these functions depend on the actin nucleation and elongation activities of formins (Bartolini et al, 2008;Andrés-Delgado et al, 2010;Madrid et al, 2010;Andrés-Delgado et al, 2012;Ramabhadran et al, 2012;Stastna et al, 2012), which have been demonstrated by investigating point mutations that impair in these activities Lu et al, 2007;Ramabhadran et al, 2012).…”
Section: Cellular Functions Of Forminsmentioning
confidence: 99%
“…52 Similarly, gastrulation defects were observed in Xenopus and zebrafish when Pfn1 expression was downregulated through antisense morpholinos. 53,54 Relevant to mammalian cell systems, it has been shown that loss of expression or disruption of ligand interactions of Pfn1 causes impaired migration/invasion and capillary morphogenesis of human vascular endothelial cells, and defects in neurite outgrowth. 24,26,55,56 Very recently, cre/lox-based gene deletion approach has been utilized to study the effect of tissue-specific loss of Pfn1 in vivo.…”
Section: Context-specific Effect Of Pfn1 In Cell Motilitymentioning
confidence: 99%
“…Knockdown of the zebrafish ortholog of DIAPH3, zdia2, by antisense morpholino oligonucleotides is lethal to the embryo before the formation of the auditory organ (22).…”
Section: Expression Of Diaph3 Protein Is Significantly Increased Inmentioning
confidence: 99%